Anti-doping - the end of sport - Møller, V.; Dimeo, P. (International Journal of Sport Policy and Politics, 2014)
We will argue that sport is essentially deteriorating under the current anti-doping campaign executed by an un-coordinated alliance between the World Anti-Doping Agency (WADA), law enforcement authorities, sports organizers and the media. We will develop our argument in three steps. We begin with a brief consideration of the fundamental characteristics that define the kind of sport WADA was established to protect. After this, we use the case of cycling to demonstrate the unplanned consequences of the current sanction system and show how it diminishes the meaning of sport before we finish the article by calling for a more rational and level-headed approach which is urgently needed to bring sport out of its current mess.